Determination of Maximum Wind Power Penetration in an Isolated Island System by Considering Spinning Reserve - Chia-An Chang; Yuan-Kang Wu; Bin-Kwie Chen (Energies, 2016)
The abundant wind resources in the Penghu area, where the capacity factor of wind turbines can reach 45%, have inspired authorities to build more wind turbines in a diesel-based power system. However, because the wind turbine output is unstable, high wind power penetration in the system may relatively affect the power quality (voltage and frequency) and reliability of the system. Previous studies have suggested that the optimal penetration level for wind power generation under the present dispatching criteria in Penghu is 26.3%. The present study suggests that the criteria for current unit scheduling should be modified; in particular, the spinning reserve (SR) capacity of the diesel engines should be increased without affecting the reliability and power quality of the power system. Such an increase could help avoid the construction of high-cost energy storage systems.